Synthesis, in silico ADMET prediction analysis, and pharmacological evaluation of sulfonamide derivatives tethered with pyrazole or pyridine as anti-diabetic and anti-Alzheimer's agents - Nagwa M. Abdelazeem; Wael M. Aboulthana; Ashraf S. Hassan; Abdulrahman A. Almehizia; Ahmed M. Naglah; Hamad M. Alkahtani (Elsevier, 2024)
Based on previous developments of our research programs in trying to find new compounds with multiple biological targets such as antioxidant, anti-diabetic, anti-Alzheimer's, and anti-arthritic agents. In the context, a novel series of sulfonamide derivatives based on the pyrazole or pyridine moieties 3a, b, 7-9, 11-13, 15a, b, and 16 were synthesized from amine compounds with sulfonyl chloride derivatives. The structures of sulfonamide derivatives were elucidated via spectroscopy (1H and 13C NMR). The sulfonamide derivatives were biologically assessed in vitro for their anti-diabetic (α-amylase and α-glucosidase inhibition) and anti-Alzheimer's (acetylcholinesterase inhibition) activities. The biological results revealed that compound 15a is a powerful enzyme inhibitor for α-amylase and α-glucosidase. Also, compound 15b demonstrated inhibitor activity against the acetylcholinesterase enzyme. The structure-activity relationship study of sulfonamide derivatives was accomplished. Furthermore, complementary in silico molecular properties, drug-likeness, ADMET prediction, and surface properties of the two more powerful derivatives 15a and 15b were fulfilled and computed. These studies recommend 15a and 15b as candidates with modifications in their structures before the in vivo assays.